Exploring experience as a market segmentation device: a case study for the Austrian tourism industry. - Bentley, R (2016)
This dissertation explores whether experience can be utilised as a market segmentation device. It tackles the huge void that exists regarding the usage of experience within tourist segmentation studies. Initially, tourism marketing literature is analysed to examine to what extent experience has penetrated this field of study. Then, more specifically, previous tourism segmentations are studied to determine the plethora of devices which have been used to create segments in the past. In order to show the effectiveness of experience as a variable, a survey was carried out which amassed 219 responses, from which the data included information regarding socio-demographics, tourism habits, activity preferences and, most importantly, the experiences tourists seek on holiday. The analysis of this data uses a host of statistical analysis methods, including factor analysis and cluster analysis, to create realistic and tangible segments which validate experience as a segmentation tool. In total, nine distinct segments are identified within the sample and the practical implications of these segments for Shepherd PR are examined. Meanwhile, the theoretical implications of this study provide a substantial platform from which future research can be undertaken into experience and its role in tourist segmentation studies.